Expression of a Recombinant Lentinula edodes Xylanase by Pichia pastoris and Its Effects on Ruminal Fermentation and Microbial Community in in vitro Incubation of Agricultural Straws - Li, Lizhi; Qu, Mingren; Liu, Chanjuan; Xu, Lanjiao; Pan, Ke; Song, Xiaozhen; OuYang, Kehui; Li, Yanjiao; Zhao, Xianghui (Frontiers in Microbiology, 2018)
Agricultural straws, such as rice straw, wheat straw, and corn straw, are produced abundantly every year but not utilized efficiently in China. An experiment was conducted to determine the effects of recombinant xylanase on ruminal fermentation and microbial community structure in in vitro incubation of these straws. The recombinant xylanase from Lentinula edodes (rLeXyn11A) was produced in Pichia pastoris. The optimal temperature and pH for rLeXyn11A were 40°C and 4.0, respectively. The rLeXyn11A featured resistance to high temperature and showed broad temperature adaptability (>50% of the maximum activity at 20-80°C). Supplemental rLeXyn11A enhanced the hydrolysis of three agricultural straws. After in vitro ruminal incubation, regardless of agricultural straws, the fiber digestibility, acetate concentration, total volatile fatty acids (VFA) production, and fermentation liquid microbial protein were increased by rLeXyn11A. Supplemental rLeXyn11A increased the ammonia-N concentration for corn straw and rice straw. High throughput sequencing and real-time PCR data showed that the effects of rLeXyn11A on ruminal community depended on the fermentation substrates. With rice straw, rLeXyn11A increased the relative abundance of fibrolytic bacteria including Firmicutes, Desulfovibrio, Ruminococcaceae and its some genus, and Fibrobacter succinogenes. With wheat straw, rLeXyn11A increased the relative abundance of Ruminococcus_1 and its three representative species F. succinogenes, Ruminococcus flavefaciens, Ruminococcus albus. With corn straw, the fibrolytic bacteria Firmicutes, Christensenellaceae_R_7_group, Saccharofermentans, and Desulfovibrio were increased by rLeXyn11A. This study demonstrates that rLeXyn11A could enhance in vitro ruminal digestion and fermentation of agricultural straws, showing the potential of rLeXyn11A for improving the utilization of agricultural straws in ruminants.